2011
DOI: 10.1088/1751-8113/44/39/395305
|View full text |Cite
|
Sign up to set email alerts
|

The extended Heine–Stieltjes polynomials associated with a special LMG model

Abstract: The extended Heine-Stieltjes polynomials associated with a special Lipkin-Meshkov-Glick (LMG) model corresponding to the standard two-site Bose-Hubbard model are derived based on the Stieltjes correspondence. It is shown that there is a one-to-one correspondence between zeros of this new polynomial and solutions of the Bethe ansatz equations for the LMG model. A one-dimensional classical electrostatic analogue corresponding to the special LMG model is established according to Stieltjes early work. It shows tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 44 publications
3
57
0
Order By: Relevance
“…It can be inferred from (22) that the spectrum of the model after the Jordan-Schwinger two-boson realization is generated from the non-linear boson-quartet excitations based on the single-boson and the boson-pairing excitations, where the single-boson excitation affects both the scaling of the energy and the boson-quartet excitations, while the boson-pairing excitation energies contribute to the total energy linearly. Moreover, as shown previously [32][33][34], though the eigenstates provided in (14) are not normalized, they are always orthogonal with…”
Section: Exact Solution For Integer J Casesmentioning
confidence: 72%
See 2 more Smart Citations
“…It can be inferred from (22) that the spectrum of the model after the Jordan-Schwinger two-boson realization is generated from the non-linear boson-quartet excitations based on the single-boson and the boson-pairing excitations, where the single-boson excitation affects both the scaling of the energy and the boson-quartet excitations, while the boson-pairing excitation energies contribute to the total energy linearly. Moreover, as shown previously [32][33][34], though the eigenstates provided in (14) are not normalized, they are always orthogonal with…”
Section: Exact Solution For Integer J Casesmentioning
confidence: 72%
“…k } with ζ = 1, 2, · · · , k + 1, corresponding to global minimums of the total electrostatic energy of the system [32]. It follows from this that the total number of these configurations is exactly the number of ways to put the k zeros into the two open intervals, which is k + 1.…”
Section: Exact Solution For Integer J Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to solve the sets of quadratic equations defined by (8) we use a combination of Taylor expansion to generate an approximative solution at g + δg and Newton's method to refine this approximation. For both methods we need to solve a linear system of equations defined by the block-N × N −matrix…”
Section: How To Proceedmentioning
confidence: 99%
“…It has been shown that either spherical or deformed mean-field plus the standard (orbit-independent) pairing interaction can be solved exactly by using the Gaudin-Richardson method [3][4][5]. The Gaudin-Richardson equations in this case can be solved more easily by using the extended Heine-Stieltjes polynomial approach [6][7][8][9]. The deformed and spherical mean-field plus the extended pairing models have also been proposed, which can be solved more easily than the standard pairing model, especially when both the number of valence nucleon pairs and the number of single-particle orbits are large [10,11].…”
Section: Introductionmentioning
confidence: 99%